Polish Judiciary and the Constitutional Fidelity. „In Judges We Trust”? - Koncewicz, Tomasz Tadeusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
As the Polish government continues to strike at the very heart of the rule of law by refusing to implement, and publish, the judgments of the Constitutional Court, the issue of legal consequences of a judgment delivered, but unpublished and/or unimplemented, comes to the fore. The primary objective of the analysis is to show how disabling the Constitutional Court and constitutional capture of checks-and-balances should translate into the case law of ordinary judges. This latter aspect received only scant attention from the academia. Ordinary courts have their own promises to fulfill when faced with the all-out capture of constitutional essentials making up Polish legal order. As we move forward, these courts should be ready to take on the mantle of quasi-constitutional courts and defend the integrity of the system. Whether they are ready to perform such systemic function is a different question altogether.
Keywords: praworządność; konstytucjonalizm; kontrola sądowa; skutek bezpośredni; wierność konstytucyjna; integralność; etos sądowy; wierność; tekst kontra kontekst; uprawnienia sędziów